2011
DOI: 10.1371/journal.pone.0018278
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Molecular Mechanisms of Traditional Chinese Medicinal Formula Si-Wu-Tang Using Gene Expression Microarray and Connectivity Map

Abstract: To pursue a systematic approach to discovery of mechanisms of action of traditional Chinese medicine (TCM), we used microarrays, bioinformatics and the “Connectivity Map” (CMAP) to examine TCM-induced changes in gene expression. We demonstrated that this approach can be used to elucidate new molecular targets using a model TCM herbal formula Si-Wu-Tang (SWT) which is widely used for women's health. The human breast cancer MCF-7 cells treated with 0.1 µM estradiol or 2.56 mg/ml of SWT showed dramatic gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(131 citation statements)
references
References 51 publications
(80 reference statements)
6
125
0
Order By: Relevance
“…Interestingly, the extracts of the Paris polyphylla plant, containing polyphyllin D, have been long used in traditional Chinese medicine for cancer treatment [72]. Their CMap analysis indicated that polyphyllin D is a trigger for estrogen receptorinduced apoptosis and mitochondria-mediated apoptotic pathways [73].…”
Section: The L1000cdsmentioning
confidence: 99%
“…Interestingly, the extracts of the Paris polyphylla plant, containing polyphyllin D, have been long used in traditional Chinese medicine for cancer treatment [72]. Their CMap analysis indicated that polyphyllin D is a trigger for estrogen receptorinduced apoptosis and mitochondria-mediated apoptotic pathways [73].…”
Section: The L1000cdsmentioning
confidence: 99%
“…Traditional Chinese medicines (TCMs) have been used in China and other Asian countries for thousands years for the prevention and treatment of a wide variety of diseases (Peng et al, 2011;Wen et al, 2011). Curcumin comes from the rhizome of Curcuma longa, and has broader pharmacological activities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is also demonstrated that XYT has a promising therapeutic value as an antiinflammatory drug. Traditional Chinese medicines (TCMs) have been used in China and other Asian countries for thousands years for the prevention and treatment of a wide variety of diseases (Wen et al, 2011). There are a large number of herbal formulations in TCMs, most of them contain a mixture of herbs, and multiple constituents are responsible for their bioactivities.…”
Section: Discussionmentioning
confidence: 99%